Data and code for "Quantifying Dynamic Tilting in Halide Perovskites: Chemical Trends and Local Correlations" - Wiktor, Julia; Fransson, Erik; Kubicki, Dominik; Erhart, Paul (Chalmers University of Technology, 2025)
This record contains data, scripts, and models associated with the publication  "Quantifying Dynamic Tilting in Halide Perovskites: Chemical Trends and Local Correlations".

Databases

The *.db files are databases with the results from density functional theory (DFT) calculations. These are sqlite databases in ase format, see here for more information. The demo-database-access.py script illustrates the most basic access.

Models

The neuroevolution potential (NEP) models described in the publication can be found in the nep-*.txt files. They can be used in conjunction with the GPUMD package. The calorine package provides a Python interface to GPUMD.

Primitive structures

Several primitive structures in extended xyz format can be found in the *.xyz files. These structures have been relaxed using the NEP models included here. The demo-for-using-structures-and-models.py script illustrates how to access the structures and models.

Tools for analyzing tilt angles

standardize-cell-orientation.pyConverts each frame in movie.xyz to the standardized cell setting and writes the resulting trajectory to movie-standardized.xyz. This is useful when working with triclinic cells.

analyze-tilt-angles-for-orthorhombic-cells.pyAnalyzes the distribution of tilt angles for each frame in a trajectory. The analysis assumes that the B-B bonds are oriented along the Cartesian coordinate system either without further rotation or after a "simple" rotation of the entire cell.

angle-analysis.ovitoOvito script that approximately implements the procedure used in analyze-tilt-angles-for-orthorhombic-cells.py.
Keywords: neuroevolution potential; tilt angles; GPUMD; density functional theory; Physical Sciences; Fysik